Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1093/sjaf/15.3.128
|View full text |Cite
|
Sign up to set email alerts
|

A Cost Index for Southern Forest Practices

Abstract: Simple forest practice cost indexes, a weighted aggregate Southern Forest Practice Cost Index (SFPCI), and a Southern Forest Employee Wage Index (SFEWI) are developed. The SFPCI measures temporal changes in average costs of a fixed "operations basket" of southern forest practices. Each forest practices's relative contribution to the SFPCI are also calculated. General trends, and internal and external factors influencing cost index changes throughout time are examined in order to provide forestry managers insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Considering the implementation of incentive-driven policies, if a forest owner participates in incentive-based cost-share programs and given the operating costs, this study assumes that engagement in collaborative efforts between two adjacent forest owners could save up to 50% of the total wildfire mitigation costs. This assumption is based on the reported costs associated with the fuel removal process by Schaaf et al [44], Dubois et al [45], and Bolding et al [46]. On the other hand, if a forest owner follows fuel stock regulations, the fuel stock in the forest must not exceed a certain amount imposed by an authority or exogenous forest-owner association.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the implementation of incentive-driven policies, if a forest owner participates in incentive-based cost-share programs and given the operating costs, this study assumes that engagement in collaborative efforts between two adjacent forest owners could save up to 50% of the total wildfire mitigation costs. This assumption is based on the reported costs associated with the fuel removal process by Schaaf et al [44], Dubois et al [45], and Bolding et al [46]. On the other hand, if a forest owner follows fuel stock regulations, the fuel stock in the forest must not exceed a certain amount imposed by an authority or exogenous forest-owner association.…”
Section: Methodsmentioning
confidence: 99%
“…Crop production and pasture/range activities use the revenue-cost ratio (FAPRI and AMAP, 2021) to complete the derivation of the net returns. Trees' planting and management costs subtracted from tree total revenues allow for optimizing discounted present values of the net return with respect to the age of trees (Dubois et al, 2001(Dubois et al, , 2003Moulton and Richards, 1990;Smidt et al, 2005;Folegatti et al, 2007;Barlow et al, 2009;Barlow and Dubois, 2011;Dooley and Barlow, 2013;Maggard and Barlow, 2017). All state net returns are weighted by the ratio of acres planted or covered by each category so that quinquennial FPR net returns are finally calculated as the arithmetic average for every 5 years of the annual observations between 1992 and 2017.…”
Section: Datamentioning
confidence: 99%
“…The first economic trend analysis of this data, covering 24 years, occurred in 1982 and found forestry practices cost rising substantially faster than both the price of southern pine lumber and the whole price index, suggesting that the cost of practicing forestry was outpacing inflation and any potential increase in the price of southern pine sawtimber [41]. A 1991 study constructed cost indices for nine commonly used forestry practices in the South for the years 1982 to 1988, creating simple price indices for each practice and developing a Southern Forest Practices Cost Index (SFPCI) as a metric for tracking changes in forestry practices cost as a conglomerate, along with a Southern Forestry Employee Wage Index (SFEWI) [42]. Using only data from private forestry firms, the study found that both the SFPCI and SFEWI rose slightly less than inflation, suggesting that forestry practices cost increases were moderating [42].…”
Section: Literature On Forest Practices Costmentioning
confidence: 99%
“…A 1991 study constructed cost indices for nine commonly used forestry practices in the South for the years 1982 to 1988, creating simple price indices for each practice and developing a Southern Forest Practices Cost Index (SFPCI) as a metric for tracking changes in forestry practices cost as a conglomerate, along with a Southern Forestry Employee Wage Index (SFEWI) [42]. Using only data from private forestry firms, the study found that both the SFPCI and SFEWI rose slightly less than inflation, suggesting that forestry practices cost increases were moderating [42].…”
Section: Literature On Forest Practices Costmentioning
confidence: 99%